Imaging criteria in neuro-oncology - Nowosielski, Martha; Wen, Patrick Y. (Seminars in neurology, 2018)
The identification of more effective therapies for brain tumors has been limited in part by the lack of reliable criteria for determining response and progression. Since its introduction in 1990, the MacDonald criteria have been used in neuro-oncology clinical trials to determine response, but they fail to address issues such as pseudoprogression, pseudoresponse, and nonenhancing tumor progression that have arisen with more recent therapies. The Response Assessment in Neuro-Oncology (RANO) working group, a multidisciplinary international group consisting of neuro-oncologists, medical oncologists, neuroradiologists, neurosurgeons, radiation oncologists, and neuropsychologists, was formed to improve response assessment and clinical trial endpoints in neuro-oncology. Although it was initially focused on response assessment for gliomas, the scope of the RANO group has been broadened to include brain metastases, leptomeningeal metastases, spine tumors, pediatric brain tumors, and meningiomas. In addition, subgroups have focused on response assessment during immunotherapy and use of positron emission tomography, as well as determination of neurologic function, clinical outcomes assessment, and seizures. The RANO criteria are currently a collective work in progress, and refinements will be needed in the future based on data from clinical trials and improved imaging techniques